ANALISIS LITERASI ENERGI SISWA SMK PROGRAM KEAHLIAN TEKNIKKETENAGALISTRIKAN - Nurdiansyah, - (2020)
The importance of energy makes energy sources especially non-renewable energy sources continue to be exploited and consumed until they are out of control and cause problems for the environment (Hamakawa, 2002). As one of the Expertise Programs which is closely related to energy use and utilization, the Electrical Engineering Expertise Program also has an important role in the energy sustainability agenda in the future. The first step in growing that role is to see the extent to which students understand about energy or also known as energy literacy. This also encourages researchers to conduct a study of the energy literacy of vocational students in the Electrical Engineering Expertise Program. The research design used in this study is quantitative descriptive, while the data obtained from the survey method by taking data through an energy literacy questionnaire involving 421 respondents. The results revealed that the level of energy literacy of students in the aspect of knowledge 32.49%, the aspect of attitude 3.72, and the aspect of behavior 3.35. These results indicate that the level of energy literacy in the aspects of attitudes and aspects of behavior is quite high, while the aspects of knowledge are still low. The relationship between the three aspects of energy literacy is only on aspects of attitude with aspects of behavior that have a fairly strong and significant relationship, which means that when students have a good attitude related to energy literacy they also have good behavior and vice versa. Whereas the aspect of knowledge has a weak relationship to the other two aspects of energy literacy, which means that when students have good knowledge, they do not necessarily have good attitudes and behavior and vice versa. The role of schools, including teachers, is not optimal enough in the development and improvement of students' energy literacy abilities. However, they still consider that energy literacy is an important thing to understand, especially for students in the Electrical Engineering Expertise Program, so that in the future the school will think of plans to increase student energy literacy. Keywords: Energy Literacy, Electricial Engineering, Vocational High Schools, Energy sustainability